A new fish, Peristedion nesium (Scorpaeniformes: Peristediidae) from Isla del Coco, Costa Rica - William A Bussing (Revista de Biología Tropical, 2010)
Several expeditions in recent years to Isla del Coco have increased the total number of species of fishes known from the island. Several of these species have been described as new endemics (Bussing 1983, 1990, 1991a, 1991b, 1997). During the 1972 R/V Searcher Expedition to Costa Rica several trawl collections were made around Isla del Coco. At five localities in depths between 110 and 180m, 86 specimens of a new species of Peristedion were taken and are described herein. A key to the four species of Eastern Pacific Peristedion is included. Rev. Biol. Trop. 58 (4): 1149-1156. Epub 2010 December 01. Varias expediciones en años recientes a la Isla del Coco han aumentado el número total de especies de peces conocidas de la isla. Se han descrito varias de estas nuevas especies como endémicas (Bussing 1983, 1990, 1991a, 1991b, 1997). Durante la Expedición R/V Searcher de 1972 a Costa Rica, se hicieron varias recolectas con redes de arrastre alrededor de la isla. En cinco localidades, con profundidades entre 110 y 145m, se capturaron ejemplares de una nueva especie de Peristedion que se describe en este trabajo. Se incluye una clave para las cuatro especies del Pacífico oriental.